Stratospheric Ozone Changes From Explosive Tropical Volcanoes: Modeling and Ice Core Constraints. Issue 11 (8th June 2020) - Ming, Alison; Winton, V. Holly L.; Keeble, James; Abraham, Nathan L.; Dalvi, Mohit C.; Griffiths, Paul; Caillon, Nicolas; Jones, Anna E.; Mulvaney, Robert; Savarino, Joël; Frey, Markus M.; Yang, Xin
Abstract: Major tropical volcanic eruptions have emitted large quantities of stratospheric sulfate and are potential sources of stratospheric chlorine although this is less well constrained by observations. This study combines model and ice core analysis to investigate past changes in total column ozone. Historic eruptions are good analogs for future eruptions as stratospheric chlorine levels have been decreasing since the year 2000. We perturb the preindustrial atmosphere of a chemistry‐climate model with high and low emissions of sulfate and chlorine. The sign of the resulting Antarctic ozone change is highly sensitive to the background stratospheric chlorine loading. In the first year, the response is dynamical, with ozone increases over Antarctica. In the high HCl (2 Tg emission) experiment, the injected chlorine is slowly transported to the polar regions with subsequent chemical ozone depletion. These model results are then compared to measurements of the stable nitrogen isotopic ratio, δ 15 N ( NO 3 − ), from a low snow accumulation Antarctic ice core from Dronning Maud Land (recovered in 2016–2017). We expect ozone depletion to lead to increased surface ultraviolet (UV) radiation, enhanced air‐snow nitrate photochemistry and enrichment in δ 15 N ( NO 3 − ) in the ice core. We focus on the possible ozone depletion event that followed the largest volcanic eruption in the past 1, 000 years, Samalas in 1257. The characteristic sulfate signal from this volcano is present in the ice core but the variability in δ 15 N ( NO 3 − ) dominates any signal arising from changes in ultraviolet from ozone depletion. Prolonged complete ozone removal following this eruption is unlikely to have occurred over Antarctica. Plain Language Summary: Chlorine in the stratosphere destroys ozone that protects the Earth from harmful ultraviolet radiation. Volcanic eruptions in the tropics can emit sulfate and chlorine into the stratosphere. Chlorine levels are currently decreasing and to understand the impact of a volcanic eruption on stratospheric ozone in a future climate, historical eruptions are a useful analog since the preindustrial climate also had low chlorine levels. Using a chemistry‐climate model, we run a set of experiments where we inject different amounts of sulfate and chlorine into the stratosphere over the tropics to simulate different types and strengths of explosive volcanoes and we find that the ozone over Antarctica initially increases over the first year following the eruption. If the volcano emits a large amount of chlorine, ozone then decreases over Antarctica in years two to four following the eruption. We also compare our results to ice core data around a large historic volcanic eruption, Samalas (1257). Key Points: The tropical volcanic eruption in the model shows that the sign of the ozone change is highly sensitive to stratospheric chlorine amounts δ 15 N(NO3 ‐) (a proxy for surface ultraviolet radiation) from the 1257 Samalas eruption is obscured by interannual variability in the ice core Any δ 15 N(NO3 ‐) signal from the Samalas eruption will be below 60 per mil. It is unlikely that prolonged complete ozone removal occurred